Aroma components analysis of "Gongniang No. 1" rose wine and distilled spirits from Weifang area of Shandong province - DING Wenhui, WANG Yilu, SHEN Huijie, ZHAO Zhichao (Zhongguo niangzao)
A rose wine and a distilled spirit were prepared from "Gongniang No. 1" grape cultivated in Weifang area of Shandong province. Aroma components of wine samples were qualitatively and quantitatively analyzed by headspace solid phase microextraction combined with full two-dimensional gas-high-throughput high-resolution mass spectrometry (HS-SPME-GC×GC-HRMS). Aroma substance activity was evaluated by odor activity value (OAV) and aroma contribution was analyzed. The results showed that a total of 76 aroma components were detected in the rose wine and the distilled spirits, 58 in the rose wine and 45 in the distilled spirits. The aroma components mainly included esters, alcohols, fatty acids, volatile phenols, aldehydes and ketones. In "Gongniang No. 1" rose wine, there were 26 aroma components that exceeded the olfactory threshold, such as ethyl acetate, ethyl butyrate, ethyl caproate and β-damastone. In distilled spirits, there were 20 aroma components that exceed the olfactory threshold, such as methyl salicylate, ethyl acetate, ethyl butyrate and β-ionone. These aroma components gave "Gongniang No. 1" rose wine and distilled spirits aromas of floral and tropical fruits.